Participatory Establishment of the Maquenque Wildlife Refuge - Chassot, Olivier (2006)
The first proposal for the establishment of the Maquenque National Park  in  the  border  area  of  Costa  Rica  with  Nicaragua  was submitted   in   1992.   Ten   years   later,   the   Ministry   of   the Environment  and  Energy  decided  to  back  up  the  Executive Committee of the San Juan-La Selva Biological Corridor with a more  integral  conservation  goal  to  lead  the  establishment  of Maquenque National Park. Thanks to significant funding from the Critical     Ecosystem     Partnership     Fund     and     Conservation International,  we  were  able  to  conduct  a  set  of  technical  and scientific  studies,  amongst  them  a  land  tenure  study  and  a diagnostic of the environmental state of the region, as main inputs to establish the management plan of the proponed area.  Together with dwellers from the buffer area, we decided to discard the park proposal and, instead of it, to work for the establishment of a protected area with the category of “national wildlife refuge”. Respecting the aforementioned process, the Maquenque National Wildlife Refuge was created in 2005. In this manner and with a clear  determination,  Costa  Rica  claimed  its  compromise  with biodiversity  and  with  the  establishment  of  a  key  conservation nexus  between  Southeast  Nicaragua  and  the  Central  Volcanic Range of Costa Rica, with a direct impact on the natural treasures of both countries and the Mesoamerican isthmus.